The Speaker’s Voice in Ahmed Al-Nehmi’s Poem "I Am Not One of You": A Pragmatic Study - Saad, Sarah Ahmed Hussein (Arts for Linguistic & Literary Studies, 2025)
This study examines the speaker’s voice in Ahmed Al-Nehmi’s poem “I Am Not One of You” through a pragmatic lens. Centered on the Palestinian cause, the poem deploys polyphony—multiple voices—to influence the addressee and inspire resistance against occupation. The most prominent voice is that of the Palestinian speaker, depicted as a symbol of resilience and national struggle. This voice encapsulates the collective suffering of a homeland and serves to persuade the Arab addressee to abandon passivity. The analysis follows a structured approach, presenting each voice in the order it appears in the poem: the poet, the land of Palestine, the Palestinian child, the Palestinian woman, Arab leaders, the resistance fighter, and finally, Palestine personified. These voices act as rhetorical tools that enhance the poem’s emotional depth and communicative power. The study concludes that the strategic use of multiple voices enables the poet to embody different perspectives while maintaining a unified message. This multiplicity functions as a pragmatic device that strengthens the poet’s communicative intent and amplifies the urgency of the political message.